Biotransformation of Cholesterol and 16α, 17α-Epoxypregnenolone and Isolation of Hydroxylase in Burkholderia cepacia SE-1. (2nd June 2016) - Zhu, XiangDong; Pang, CuiPing; Cao, Yuting; Fan, Dan
Abstract : The metabolism of cholesterol is critical in eukaryotes as a precursor for vitamins, steroid hormones, and bile acids. Some steroid compounds can be transformed into precursors of steroid medicine by some microorganisms. In this study, the biotransformation products of cholesterol and 16 α, 17 α -epoxypregnenolone produced by Burkholderia cepacia SE-1 were investigated, and a correlative enzyme, hydroxylase, was also studied. The biotransformation products, 7 β -hydroxycholesterol, 7-oxocholesterol, and 20-droxyl-16 α, 17 α -epoxypregn-1, 4-dien-3-one, were purified by silica gel and Sephadex LH-20 column chromatography and identified by nuclear magnetic resonance and mass spectroscopy. The hydroxylase was isolated from the bacterium and the partial sequences of the hydroxylase, which belong to the catalases/peroxidase family, were analyzed using MS/MS analyses. The enzyme showed activity toward cholesterol and had a specific activity of 37.2 U/mg of protein at 30°C and pH 7.0.